Laying the Foundation: How Substrate Choice Influences Kelp Reforestation Success - Tomás F. Pinheiro; Sílvia Chemello; Isabel Sousa-Pinto; Tânia R. Pereira (Journal of Marine Science and Engineering)
Over recent decades, widespread declines of kelp forests have been reported along the European coast, prompting the need for effective and scalable restoration strategies. The green gravel technique, in which kelp gametophytes are seeded onto small rocks and cultivated in the lab before being outplanted, has shown promising results. In this study, we tested the effects of four commonly available substrates—granite, limestone, quartz, and schist—on the early development of Laminaria ochroleuca recruits under optimal laboratory conditions. All substrates supported gametophyte adhesion and sporophyte development. By week 6, quartz promoted the greatest recruit length (1.25 ± 0.16 mm), with quartz and limestone (1.54 ± 0.17 and 1.58 ± 0.14 mm, respectively) showing the best overall performance by week 7. Final recruit densities were similar across substrates, indicating multiple materials can support early development. Quartz and limestone showed both biological effectiveness and practical advantages, with limestone emerging as the most cost-effective option. Substrate selection should consider not only biological performance but also economic and logistical factors. These findings contribute to refining green gravel protocols and improving the feasibility of large-scale kelp forest restoration, although field validation is necessary to assess long-term outcomes under natural conditions.